Legal Certainty in the Termination of Prosecution Based on Restorative Justice: A Study at the Gunungsitoli District Prosecutor’s Office - Richisandi Sibagariang; Triono Eddy; Adi Mansar (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study examines legal certainty in the implementation of the termination of criminal prosecutions based on restorative justice, with a particular focus on the jurisdiction of the Gunungsitoli District Prosecutor’s Office. As a state governed by the rule of law, Indonesia maintains a legal enforcement system that seeks to balance the principles of legal certainty, justice, and expediency. The enactment of Attorney General Regulation (PERJA) No. 15 of 2020 concerning the Termination of Prosecution Based on Restorative Justice provides a juridical basis for prosecutors, as holders of the dominus litis principle, to exercise prosecutorial discretion in resolving criminal cases. Employing a normative juridical and empirical socio-legal research approach with a descriptive-analytical design, this study analyzes the legal framework, implementation process, and challenges encountered in the application of restorative justice. The findings indicate a significant increase in the settlement of criminal cases through restorative justice at the Gunungsitoli District Prosecutor’s Office, rising from four cases in 2023 to nine cases in 2024. The principal obstacles include the failure to satisfy substantive and procedural requirements, conflicts of interest arising from disproportionate compensation demands, and the absence of willingness among the parties to reach an amicable settlement. To address these challenges, the study recommends strengthening the capacity of Prosecutor Facilitators, enhancing institutional coordination and harmonization, and establishing restorative justice counseling centers to facilitate the psychological recovery of both victims and offenders. These measures are expected to improve the effectiveness of restorative justice while ensuring greater legal certainty in the exercise of prosecutorial discretion.